Sciatic Nerve Injection Palsy in Children - HARSH, Viraat; CHENGAZHACHERRIL, Romy B; SHARMA, Kanika; KALAKOTI, Piyush; GUPTA, Utkarsh; AHMAD, Waqar; KUMAR, Anil (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Harsh V, Chengazhacherril R.B, SharmaK, Kalakoti P, Gupta U, Ahmad W, Kumar A. Sciatic Nerve Injection Palsy in Children. Iran J Child Neurol. Autumn 2016; 10(4):86-87. Letter to Editor Pls see PDF file. References 1. Toopchizadeh V, Barzegar M, Habibzadeh A. Sciatic Nerve Injection Palsy in Children, Electrophysiologic Pattern and Outcome: A Case Series Study. Iran J Child Neurol 2015 Summer;9(3):69-72. 2. Sunderland S. Miscellaneous causes of nerve injury. London: Churcill Livingstone; 1991. 3. Lehmann HC, Zhang J, Mori S, Sheikh KA. Diffusion tensor imaging to assess axonal regeneration in peripheral nerves. Exp Neurol 2010;223(1):238-44. 4. Takagi T, Nakamura M, Yamada M, Hikishima K, Momoshima S, Fujiyoshi K, et al. Visualization of peripheral nerve degeneration and regeneration: monitoring with diffusion tensor tractography. NeuroImage 2009 ;44(3):884-92. 5. Barry JM, Harsh V, Kumar A, Patil S. Injection nerve palsy: What’s to blame? J Neurosci Rural Pract 2013;4:481. 6. Greensmith JE, Murray WB. Complications of regional anesthesia. Current opinion in anaesthesiology. 2006;19(5):531-7. 7. Barry JM, Harsh V, Patil S. Are our intramuscular injections nerve-friendly? What are we missing? Simple techniques to prevent, recognize and manage nerve injection injuries. Int J Stud Res 2014;4(2):25-8.